Efforts to Propagate Sorghum In Vitro to Support Local Food - Aisyah, Siti; Hazmi, Muhammad; Murtiyaningsih, Hidayah (International Applied Science, 2024)
indonesia is a country known for its abundant biodiversity. however, the majority of its people still make rice as a daily staple food, making the price of rice continue to increase until it is difficult to reach by low-income people. therefore, it is necessary to develop alternative local food to replace rice to avoid a food crisis. One of the alternative plants is sorghum. Because sorghum has many benefits besides as food as well as bioenergy. That way it is necessary to make efforts to develop sorghum, one of which is by means of embryogenic callus tissue culture techniques by adding a concentration of 2,4-D. This research was conducted in the Laboratory of Nutraseutical and Pharmaseutical Division of Center for Development of Advancd Science and Technologies (CDAST) UPA Waste Management and Integrated Laboratory, University of Muhammadiyah Jember by using Completely Randomized Design (CRD) with a single factor namely A0 (control), A1 1 ppm, A2 2ppm, A3 3ppm, A4 4 ppm which was repeated 3 times. The variables under observation are the callus's color, texture, percentage, and time of formation. According to the study's findings, the application of 4 ppm 2,4-D produced the best results when compared to other 2,4-D treatments. These treatments were able to produce callus at a rate of 4.11 his, 100% of the total number of callus, crumbly texture, and pale yellowish color.